Maternal immune activation-induced proBDNF-mediated neural information processing dysfunction at hippocampal CA3-CA1 synapses associated with memory deficits in offspring - Sun, Wei; Mei, Yazi; Li, Xiaoliang; Yang, Yang; An, Lei (Frontiers in Cell and Developmental Biology, 2022)
Prenatal exposure to maternal infection increases the risk of offspring developing schizophrenia in adulthood. Current theories suggest that the consequences of MIA on mBDNF secretion may underlie the increased risk of cognitive disorder. There is little evidence for whether the expression of its precursor, proBDNF, is changed and how proBDNF-mediated signaling may involve in learning and memory. In this study, proBDNF levels were detected in the hippocampal CA1 and CA3 regions of male adult rats following MIA by prenatal polyI:C exposure. Behaviorally, learning and memory were assessed in contextual fear conditioning tasks. Local field potentials were recorded in the hippocampal CA3-CA1 pathway. The General Partial Directed Coherence approach was utilized to identify the directional alternation of neural information flow between CA3 and CA1 regions. EPSCs were recorded in CA1 pyramidal neurons to explore a possible mechanism involving the proBDNF-p75NTR signaling pathway. Results showed that the expression of proBDNF in the polyI:C-treated offspring was abnormally enhanced in both CA3 and CA1 regions. Meanwhile, the mBDNF expression was reduced in both hippocampal regions. Intra-hippocampal CA1 but not CA3 injection with anti-proBDNF antibody and p75NTR inhibitor TAT-Pep5 effectively mitigated the contextual memory deficits. Meanwhile, reductions in the phase synchronization between CA3 and CA1 and the coupling directional indexes from CA3 to CA1 were enhanced by the intra-CA1 infusions. Moreover, blocking proBDNF/p75NTR signaling could reverse the declined amplitude of EPSCs in CA1 pyramidal neurons, indicating the changes in postsynaptic information processing in the polyI:C-treated offspring. Therefore, the changes in hippocampal proBDNF activity in prenatal polyI:C exposure represent a potential mechanism involved in NIF disruption leading to contextual memory impairments.